Design For Longevity and Design For X: Concepts, Applications, and Perspectives - Yunia Dwie Nurcahyanie; Linda Dwi Rohmadiani (Tibuana, 2023)
The scientific development of Design For X is very rapid. The definition of Design For X in question is Design for specific purposes. Starting from Design For Manufacture, Design For Sustainability developed into Design For Longevity. The goal of Design For Longevity is design to extend product lifetime.Design For Longevity is a concept where products with a short lifespan are strived for a longer life. As a new concept that develops in a fast-paced era and products shift with short trends, the DfL application is indispensable.This study used a bibliometric study approach using NVIVO analysis and combined with a descriptive qualitative study the relationship between Design For Longevity and Design For X.